Continuous Flow Catalytic Reductive Amination of Carbonyl Compounds to Primary Amines with Carbon‐Coated Co@CS Catalyst under Mild Conditions - Mi, Siyi; Liu, Yulong; Liu, Jianguo; Pyo, Sang-Hyun ; 0000-0002-5037-2748 (ChemPlusChem, 2025)
Reductive amination is crucial for synthesizing amines in pharmaceutical and industry, yet selectively producing primary amines on a large scale remains challenging. This work presents a continuous-flow reductive amination process using benzaldehyde with NH3 and H2 as the nitrogen sources and reductant. A cobalt catalyst supported on nitrogen-doped carbon derived from chitosan (Co@CS) was developed. After optimization, a primary amine yield exceeding 99% was achieved under mild reaction conditions. The catalyst demonstrated excellent stability in long-term tests and with various substrates, including the biomass lignin-derived vanillin. Compared to batch reactors, theflow reactor provided superior selectivity. This catalytic flow process minimizes waste, enhances atom economy, avoids hazardous chemical, and improves energy efficiency. The use of a renewable chitosan feedstock and a safer process aligns with multiple principles of green chemistry. The exceptional heat and mass transfer in the Flow system offers an effective strategy for the large-scale production of primary amines from biomass platform compounds.